2019 IEEE/CVF International Conference on Computer Vision Workshop (ICCVW) 2019
DOI: 10.1109/iccvw.2019.00295
|View full text |Cite
|
Sign up to set email alerts
|

NADS-Net: A Nimble Architecture for Driver and Seat Belt Detection via Convolutional Neural Networks

Abstract: A new convolutional neural network (CNN) architecture for 2D driver/passenger pose estimation and seat belt detection is proposed in this paper. The new architecture is more nimble and thus more suitable for in-vehicle monitoring tasks compared to other generic pose estimation algorithms. The new architecture, named NADS-Net, utilizes the feature pyramid network (FPN) backbone with multiple detection heads to achieve the optimal performance for driver/passenger state detection tasks. The new architecture is va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…The test results showed that this proposed method increased the average correct detection and reduced the training time compared to Alexnet, VGGNet-16, and GoogLeNet. Chun et al proposed a CNN model named NADS-Net (A Nimble Architecture for Driver and Seat Belt Detection via Convolutional Neural Networks) using the feature pyramid network (FPN) backbone method and multiple detection heads [Chun et al, (2019)]. The method was applied under different demographics, appearances, and illumination.…”
Section: Non-handcrafted Featurementioning
confidence: 99%
“…The test results showed that this proposed method increased the average correct detection and reduced the training time compared to Alexnet, VGGNet-16, and GoogLeNet. Chun et al proposed a CNN model named NADS-Net (A Nimble Architecture for Driver and Seat Belt Detection via Convolutional Neural Networks) using the feature pyramid network (FPN) backbone method and multiple detection heads [Chun et al, (2019)]. The method was applied under different demographics, appearances, and illumination.…”
Section: Non-handcrafted Featurementioning
confidence: 99%
“…There are large data sets like Common Objects in Context (COCO) [9], which provide a large amount of key point annotations of persons in various positions. A notable attempt to process images, which utilizes the COCO data set, was proposed in [10]. Here the authors detected the seat belt with a semantic segmentation and conducted a human posture estimation by detecting the key points of a person.…”
Section: Introductionmentioning
confidence: 99%
“…However, pose estimation networks for IVMS have not improved much. Only a few networks (Okuno et al 2018;Yuen and Trivedi 2018;Chun et al 2019;Heo et al 2020) have attempted to assess the performance in an invehicle environment, and even those have focused solely on 2D pose estimation. (Okuno et al 2018) proposed an architecture that estimated human pose and face orientation for an autonomous driving system that consisted of only three convolutional layers and a fully connected layer; through this shallow network, it can perform real-time processing.…”
Section: Introductionmentioning
confidence: 99%
“…Clothes Jacket, long-sleeve short-sleeve winter clothes 34% 33% 33% (Yuen and Trivedi 2018) suggested predicting only the arms of the driver and passengers; this network used partial affinity fields (PAF) from (Cao et al 2017). (Chun et al 2019) has the most similar architecture to our proposed network; they performed 2D pose estimation and seat-belt segmentation and used PAF to estimate 2D keypoints, but they only estimated body keypoints without face keypoints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation